China in Africa: a critical literature review. Issue 1 (7th March 2016) - Ado, Abdoulkadre; Su, Zhan
Abstract : Purpose: – The purpose of this paper is to critically assesses the major contributions to the academic literature on China's increased focus on Africa, from 2001 to 2011. It discusses the key trends concerning China's presence in Africa and draws conclusions on the significance of the studies by emphasizing and contrasting the prevailing positions. Design/methodology/approach: – Based on a qualitative approach using an integrative and comprehensive literature review, the authors performed a content analysis of high-impact, peer-reviewed papers. Findings: – The paper questions and repositions some of the existing controversies. The results from existing studies remain questionable, requiring further clarification and more theoretical backing. It, moreover, highlights the notion that behind the explicit neutrality views of China's presence in Africa, implicit assumptions may exist. These are often the differences in narratives conveyed by Western and Southern stakeholders. Research limitations/implications: – Most of the conclusions drawn from this paper need to be re-explored and supported by additional research. This could be done by widening the scope of the analysis. Studies need to provide more empirical support for their assertions through quantitative data and evidence-based qualitative analyses –: all within a framework that considers more cultural, social and historical dimensions. The paper also suggests that an institutionally based view appears most relevant in better explaining China in Africa. Originality/value: – This paper reviews a decade of research on China in Africa and presents a snapshot of the current state of knowledge. It also raises concerns to be analyzed by future research and proposes new avenues for better understanding China's presence in Africa.